An Evaluation of English Language Textbook: Interlanguage English for Senior High School Students - Muhammad Affan Ramadhana; Opik Dwi Indah; Suhardi Suhardi (Universitas Cokroaminoto Palopo, 2019)
English Language Teaching (ELT) textbooks serve as the basis for many language inputs that learners receive and language practices that occur in the classroom. They may provide the basis for ideas and instructional activities as well as giving teachers rationales for what they do. The objective of this analysis is to know about how much a textbook meets the requirements of a good EFL textbook. The evaluation checklist used in this paper is the modification of Cunningsworth’s (1995) checklist developed by Al-sowat (2012). There are nine issues of textbook evaluating in this checklist: (1) layout and physical appearance; (2) content; (3) objectives; (4) language type; (5) skills; (6) activities and tasks; (7) structure and vocabulary; (8) culture values; and (9) teacher's needs.